Movements and trends in intensive care pain treatment and sedation: What matters to the patient?. Issue 7 (21st January 2020) - Wøien, Hilde
Abstract: Background: Oversedation, delirium and immobilisation in the intensive care unit are associated with increased length of stay in the unit. Routines of systematic pain and sedation assessment and the use of valid tools are highly stressed in international guidelines. For improving the quality of pain treatment and sedation in a Norwegian intensive care unit, in 2009–2015, we compared supplementation with an analgosedation approach and the existing systematic approach, measured by the adherence to current international pain, sedation and delirium guidelines. Methods: In a longitudinal study following the Standards for Reporting Implementation Studies, pain, sedation, delirium and mobilisation data from patients' complete intensive care unit stays, encompassing three separate periods of 4–6 months, were compared. The primary outcome was adherence to current protocol including assessment and documentation of patients' level of pain, sedation and prevalence of delirium at least every 8 hr, early mobilisation and titration towards a light level of sedation. Results: We included 205 patients, corresponding to 1, 607 patient intensive care unit days. The patient sedation levels, measured by the Richmond Agitation and Sedation Scale, decreased significantly, from −2.2 in 2009–−1.7 in 2015, so did the amount of administrated propofol. Mean pain scores measured by the numeric rating scale during activity were maximum 3.1 in 2014, decreasing to 2.2 in 2015. In patients not able to self‐report, pain mean scores were 1.7 in 2014 and 1.6 in 2015, measured by the Critical Care Pain Observational Tool. The number of patients unable to assess for delirium decreased significantly. By discounting the group of patients unable to assess, the prevalence of delirium varied from 32%, 25% and 33%. Conclusion: The goal of having an awake patient able to cooperate, with acceptable levels of pain, was gradually achieved during a 6‐year period. The results showed that pain treatment and sedation in the intensive care unit primarily succeeded in the setting of an established routine of systematic assessment and documentation. Relevance to clinical practice: The results of the study draw attention to pain treatment, sedation and delirium in intensive care patients, as well as implementation strategies aimed at achieving healthcare personnel's adherence to international guidelines in clinical practice.